2015
DOI: 10.4081/gh.2015.306
|View full text |Cite
|
Sign up to set email alerts
|

Estimating malaria burden in Nigeria: a geostatistical modelling approach

Abstract: This study has produced a map of malaria prevalence in Nigeria based on available data from the Mapping Malaria Risk in Africa (MARA) database, including all malaria prevalence surveys in Nigeria that could be geolocated, as well as data collected during fieldwork in Nigeria between March and June 2007. Logistic regression was fitted to malaria prevalence to identify significant demographic (age) and environmental covariates in STATA. The following environmental covariates were included in the spatial model: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 25 publications
7
33
1
Order By: Relevance
“…The result of this study is a strong evidence that malaria is still highly prevalent in many urban communities including Ibadan South West Local Government Area of Oyo State, Nigeria. The high prevalence of 55% with mean (S.D) parasite density of 1814.70 (1829.117) parasite/µL of blood is an indication that Ibadan is a high-risk area for malaria transmission since it falls within Nigeria malaria risk map estimates of less than 20% in certain zone to more than 70% in other zones [15]. This is supported by other studies reported from Ibadan [8,16,17].…”
Section: Discussionsupporting
confidence: 75%
“…The result of this study is a strong evidence that malaria is still highly prevalent in many urban communities including Ibadan South West Local Government Area of Oyo State, Nigeria. The high prevalence of 55% with mean (S.D) parasite density of 1814.70 (1829.117) parasite/µL of blood is an indication that Ibadan is a high-risk area for malaria transmission since it falls within Nigeria malaria risk map estimates of less than 20% in certain zone to more than 70% in other zones [15]. This is supported by other studies reported from Ibadan [8,16,17].…”
Section: Discussionsupporting
confidence: 75%
“…In this study, the prevalence rate obtained is consistent with studies conducted in Plateau State [32], Niger [33], Benue [34] and Ebonyi State [35]. This differential pattern is supported by malaria risk maps which shows that malaria prevalence in Nigeria varied from less than 20% in certain areas to over 70% in others [3]. In other sub-Saharan countries endemic for malaria, the prevalence rate obtained in this study was similar to that reported in the Democratic Republic of the Congo [36], Equitorial Guinea [37], Mozambique [38] and Papua, New Guinea [39].…”
Section: Discussionsupporting
confidence: 90%
“…However, the distribution of malaria risk and its prevalence at the State and local government levels is heterogeneous. Considerable variations have been reported in the proportion of positive cases of malaria between study populations sampled from forest and the savanna ecological belts of Nigeria as well as between the States and the Local Government Areas (LGAs) within a State [3][4][5]. Out of the 493 children aged 6 -59 months examined by RTD in the forest zone, 37.7%-46.9% were positive for malaria parasites compared to 53%-66.6% in the savanna.…”
Section: Introductionmentioning
confidence: 99%
“…Even if their contribution to the difference of malaria risk among sub-Saharan African children were very small, the quantity of rainfall, temperature and density of population were most important community factors for malaria risk. Study of Onyiri N carried in Nigeria has found similar result as us using a geostatistical approach (Onyiri 2015).…”
Section: Discussionsupporting
confidence: 69%